The Repetitive Detection of Toluene with Bioluminescence Bioreporter Pseudomonas putida TVA8 Encapsulated in Silica Hydrogel on an Optical Fiber - Kuncová, Gabriela; Ishizaki, Takayuki; Solovyev, Andrey; Trögl, Josef; Ripp, Steven (Materials (Basel, Switzerland), 2016)
Living cells of the lux-based bioluminescent bioreporter Pseudomonas putida TVA8 were encapsulated in a silica hydrogel attached to the distal wider end of a tapered quartz fiber. Bioluminescence of immobilized cells was induced with toluene at high (26.5 mg/L) and low (5.3 mg/L) concentrations. Initial bioluminescence maxima were achieved after >12 h. One week after immobilization, a biofilm-like layer of cells had formed on the surface of the silica gel. This resulted in shorter response times and more intensive bioluminescence maxima that appeared as rapidly as 2 h after toluene induction. Considerable second bioluminescence maxima were observed after inductions with 26.5 mg toluene/L. The second and third week after immobilization the biosensor repetitively and semiquantitatively detected toluene in buffered medium. Due to silica gel dissolution and biofilm detachment, the bioluminescent signal was decreasing 20-32 days after immobilization and completely extinguished after 32 days. The reproducible formation of a surface cell layer on the wider end of the tapered optical fiber can be translated to various whole cell bioluminescent biosensor devices and may serve as a platform for in-situ sensors.
Keywords: whole cell bioreporter; encapsulation; bioluminescent biosensor; optical fiber biosensor; silica gel